“Principales plagas que afectan los cultivos de cebolla de bulbo (Allium cepa L.) en la parroquia La Paz, cantón Montúfar, provincia de Carchi, 2019” - Carrillo Mayanquer, Pedro Fidel (2019)
SUMMARY The present investigation was carried out in the parish of La Paz, Montúfar canton, province of Carchi, since it is an agricultural area that stands out in the cultivation of bulb onions. For the development of the work a format of focused questions was made to determine the pests that occur in the cultivation of onion, a participatory survey was conducted to farmers in the area with questions such as years of crop management, planted area, pests and control of these, plaguidas that applies, etc. The results obtained helped to understand the reality of the area, that most of the producers have more than 30 years managing the onion crop, in addition that they have an average of areas dedicated to the cultivation of 1 hectare, but with poor management and not Economically reach the estimated. In addition, to present presence and strong incidence of thrips since it has monocultures and does not rotate crops; In addition to the strong application of active ingredients more than yellow stripe than blue, finally a certain part of the crop is stressed by the applications against said pest, and may cause crop losses. Keywords: bulb onion, pesticides, producers, pests.